Environmental Awareness of University Science Students and Its Role in Sustainable Development - Harahap, Lia Junita (Bioedunis Journal, 2025)
Science students play a vital role in the advancement of information and technology; therefore, environmental awareness is a crucial component of sustainable behavior. This study aims to examine the level of environmental awareness among science students and the factors influencing it. A descriptive qualitative approach was employed, with data collected through observations, interviews, and literature reviews. The research respondents consisted of science students from the biology, chemistry, and physics study programs. The findings indicate that science students generally demonstrate a moderate level of environmental awareness, particularly in terms of knowledge. However, this awareness is not yet fully reflected in strong attitudes and consistent pro-environmental behaviors in daily life. Therefore, sustained efforts by educational institutions are necessary to enhance students’ environmental understanding and active participation in environmental protection.